Post‐mortem recovery, in vitro maturation and fertilization of fallow deer (Dama dama, Linnaeus 1758) oocytes collected during reproductive and no reproductive season. Issue 10 (2nd August 2020) - Uccheddu, Stefania; Pintus, Eliana; Garde, Jose Julian; Fleba, Lidia; Muzzeddu, Marco; Pudda, Flavia; Bogliolo, Luisella; Strina, Alessandro; Nieddu, Stefano; Ledda, Sergio
Abstract: Habitat degradation leads to small and fragmented populations, lower genetic variability and fertility overtime. Assisted reproductive techniques represent important tools to cope with the dramatic loss of biodiversity. Fallow deer ( Dama dama ), beyond its high commercial value and wide distribution, may represent the most suitable model to study endangered cervids. In this study, oocytes were recovered post‐mortem from fallow deer during the breeding and no breeding seasons and were in vitro matured (IVM). The ability of cryopreserved thawed sperm samples recovered by electroejaculation from four adult males was tested by in vitro fertilization of IVM oocytes. The number of oocytes collected per ovary did significantly vary across seasons from 6.2 ± 0.92 during breeding season to 10.4 ± 1.26 during no breeding season ( p = .006). Oocytes collected during the breeding season showed higher in vitro fertilization rate compared to the no breeding season ( p = .045). However, no embryos reached the blastocyst stage. Semen samples obtained by electroejaculation were successfully cryopreserved, although the cryopreservation process negatively affected most kinetic parameters, mainly at 2 hr post‐thawing. Moreover, the percentage of rapid spermatozoa significantly decreased between fresh samples and at 2 hr post‐thawing, whereas the percentage of slow spermatozoa increased across the same period ( p < .05). Our study provides the logistic steps for the application of assisted reproductive techniques in fallow deer and might be of great interest for genetic resource bank planning.